2017
DOI: 10.1186/s40317-016-0116-5
|View full text |Cite|
|
Sign up to set email alerts
|

Interpreting vertical movement behavior with holistic examination of depth distribution: a novel method reveals cryptic diel activity patterns of Chinook salmon in the Salish Sea

Abstract: Aquatic organisms exhibit a variety of diel changes in vertical movement that are investigable through the use of biotelemetry. While certain species do not change their movements between day and night, others exhibit diel vertical migration (DVM) or a diverse range of diel activity patterns (DAPs). Consequently, day-night differences in depth distribution may be stark and easily detectable, or more subtle and difficult to identify. To augment the discovery and classification of cryptic diel vertical movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Salmon may be using daylight in surface waters for foraging or navigation and/or retreating deeper at night to avoid noc- SST qC Tanaka et al, 2000;Todd et al, 2022;Wilson et al, 2014). Two tagging studies also found that the deepest Chinook salmon dives occurred at night; however, other studies have observed opposite and variable patterns (Arostegui et al, 2017;Courtney et al, 2019;Hinke, Foley et al, 2005). We add broader spatial and temporal evidence for Chinook salmon diel depth-use behaviours of moving deeper at night, which increased overlap with deeper-dwelling hake at the most common fishing depths of the hake fishery.…”
Section: Discussionmentioning
confidence: 99%
“…Salmon may be using daylight in surface waters for foraging or navigation and/or retreating deeper at night to avoid noc- SST qC Tanaka et al, 2000;Todd et al, 2022;Wilson et al, 2014). Two tagging studies also found that the deepest Chinook salmon dives occurred at night; however, other studies have observed opposite and variable patterns (Arostegui et al, 2017;Courtney et al, 2019;Hinke, Foley et al, 2005). We add broader spatial and temporal evidence for Chinook salmon diel depth-use behaviours of moving deeper at night, which increased overlap with deeper-dwelling hake at the most common fishing depths of the hake fishery.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, these extreme bounce‐diving behaviours may seem remarkable to terrestrially adapted humans who may naturally expect to see mostly horizontally oriented prey‐hunting activities such as predominate in the terrestrial world. But even chinook salmon ( Onchoryncus tshawytscha , Salmonidae) operating inside the confines of Puget Sound (in Washington State, USA) appear to employ a form of bounce diving (Arostegui et al, 2017). Apparently, something we are not expecting seems to be going on in an important manner in the submerged ‘other world’ of the ocean.…”
Section: The Trophic Web Within a Vambush Structurementioning
confidence: 99%
“…The variable and discontinuous occurrence of diel diving behaviors are similar to that of the only other electronic tagged Chinook salmon (n = 3) in the central Bering Sea (Walker and Myers 2009;Walker unpublished data) and Southeast Alaska (Murphy and Heard 2001;Murphy and Heard 2002). Further south, studies on Chinook salmon off the coast of Oregon, California, and the Salish Sea have all suggested that the presence/absence of diel vertical behaviors is correlated to multiple factors, including season and geographic location (Arostegui et al 2017;Hinke et al 2005b), which may be driven by foraging, thermoregulation, and/or predator avoidance.…”
Section: Depth and Temperature Occupancymentioning
confidence: 99%